Double-layer anti-reflection coating of SiO2–TiO2/SiO2–TiO2-PEG300 with high transmittance and super-hydrophilicity - Yong Shuai Wei; Shao Hui Xu; Li Gang Yuan; Biao Wang; Shu Li Liu; Guang Tao Fei (Materials Research Express, 2020)
A highly transparent and super-hydrophilic double-layer anti-reflection coating was prepared by a simple and economical sol-gel method based on the glass substrate. The bottom and top layer were respectively made with SiO _2 –TiO _2 sol and SiO _2 –TiO _2 -PEG300 sol. The average transmittance of the substrate coated with the double-layer coating is increased by 7% up to 97.4% in the visible light band, and the peak transmittance reaches 99% at about 550 nm. In addition, double-layer anti-reflection coating shows a good super-hydrophilic self-cleaning performance, and the transmittance of the coating can be restored by simple washing with water. Furthermore, due to the existence of anatase TiO _2 , the composite coating can restore the super-hydrophilicity damaged by dust under UV light.